Blank and void vote of students from a Peruvian university in the 2016 Peruvian general election - Flores Rivas, Víctor Ricardo (2018)
The objective of the study was to analyze the tendency to vote blank and void in students of the San Martín de Porres University, in the 2016 general elections in Peru. The research with qualitative approach, inductive method and with case study design, had as a sample of 10 students from the V cycle Faculty of Communication Sciences, Tourism and Psychology of the San Martin de Porres University, to whom in-depth interviews were conducted. The results revealed that the tendency to vote blank and null was the consequence of a reaction of the students to the trajectory of the political actors, interpreted as negative; the actions of the political parties and their candidates led to the distancing of the young electorate. In conclusion, the students voted blank or null to express their discontent with the participating political parties and candidates, and ignore the electoral regulations regarding blank and null votes.